Baptized Georgian: religious conversion to christianity in autonomous Ajaria - Pelkmans, Mathijs (Working papers, 2005)
In the Caucasus as elsewhere in the former Soviet Union, religion gained important momentum in the decade following the demise of communism. But while the renewed importance and visibility of religion is often explained as a return to pre-Soviet religious practice, in Ajaria – Georgia’s southwestern Autonomous Republic – the religious dynamics radically contest this explanation. Whereas before the Soviet era Ajarians adhered to Islam, an accelerating process of conversion to Christianity was observable in the years following the Soviet collapse. This paper looks at inhabitants of ‘Muslim’ Ajaria who have converted to Christianity, arguing that their conversion can be understood as an attempt to realign history and community with a strong sense of national identity. But although the intention of conversion was to restore historical and societal incongruities, the act of baptism was often disruptive in nature. To soften the resulting tensions with neighbors and families, the converts mobilized a host of metaphors that evoked the historical Christian legacy, demonized the ‘other’ embodied in the Turk or the Ottoman epoch, and pointed to the progressive nature of Christianity and its role in alleviating Ajaria’s ‘backwardness’. However, these ideologically informed narratives could only partly resolve the tensions involved in conversion. It was only by mobilizing ancestors as metaphors and symbolic actors in conversion that national discourses could be effectively integrated in social life and that disruptions of genealogy could be partly restored.